'ORGANIC TEMPER' AND THE EARLY NEOLITHIC POTTERY PRODUCTION: INTERPRETATIONAL CHALLENGES. Issue 2 (14th December 2020) - Dzhanfezova, Tanya
ABSTRACT: Well‐preserved plant remains found in clay bodies of Early Neolithic pottery of Southeastern Europe have been largely understudied. The characteristics and provenance of this 'organic temper' remain mostly unknown, making interpretations obscure. Based on a range of research methods, this article explores the macro and micro plant remains within the pottery clays, considering such aspects as the use of domesticated versus wild plants and actual functional temper versus organic inclusions as background noise. This innovative approach is applied to explore three different Early Neolithic Balkan sites, demonstrating the importance in distinguishing between (a) deliberate addition of selected temper as a technological prerequisite; (b) sporadic occurrence of plant parts in (domestic) areas where pottery was made, (c) natural characteristics of the local clays containing organics and used as raw materials, and (d) plant use pointing towards more specific pottery‐making techniques. Possible misinterpretations and pitfalls are discussed in using the applied integrated methodology, thus revealing crucial details on the variability of the technological approaches applied during the Early Neolithic of Southeastern Europe.